Penerapan Product Knowledge dan Strategi Up Selling dalam Sistem Penjualan Toko Online dengan Pendekatan Customer Relationship Management - Hardini Novianti; Mira Afrina; Ali Ibrahim; Ahmad fali oklilas; Dicha Pratiwi; Nabila Hidayati; Nurullah Marina Kelana; Opi Hernayanti; Septiani Aulia Putri (Jurnal Sistem Informasi, 2022)
Nisa Florist is one of the UUKM that provides products and services in the form of snack flower bouquets, flower bouquets, money flower bouquets, hijab flower bouquets, balloon bouquets and so on. Nisa Florist uses social media Instagram as a medium to market her products and services, but the distribution of product information is still not widely reached by the public. If this situation is not corrected, there will be a risk of declining customers, customer loyalty and the ability of Nisa's florists with other competitors to decrease. Therefore, to answer the above problems, the implementation of CRM with up selling and cross selling strategies is expected to be able to provide solutions to existing problems. This research produces a website. the website that has been built can help customers to transact and increase sales at Nisa Florist Palembang. With a CRM-based website with an up-selling strategy, it can increase revenue at Nisa Florist.